The Antibiotics Group Aminoglycosides and Macrolides on Beef in Bali - Siswanto Siswanto; I Nyoman Sulabda (Institute for Research and Community Service, Udayana University, 2019)
Animal products may contain certain ingredients that are not good for human health, such as antibiotic residues. The aim of this research is to know the residue of aminoglycoside and macrolide group antibiotics in Bali beef marketed in Bali-Indonesia. The study used 60 samples of meat from merchant in five different markets: Negara, Tabanan, Denpasar, Singaraja, and Klungkung, where each market was taken 12 samples. Screening tests used to determine antibiotic residues in meat. The results showed only 4 positives from 60 samples containing antibiotics, aminoglycoside 2 sempels (3.33%) and marcrolide 1 sempel (1.67%).